(untitled) (TAJ: Journal of Teachers Association, 2020)
Background & objective: Impact of Nephrotic syndrome due to relapse on children and their families is so diverse and extreme that causes serious physical and mental health problems for a long time. Repeated Hyperlipidemia and frequent long term steroid treatment in relapsed cases add more burdens on already fragile health of these children. Materials & Methods: This descriptive, observational study was carried out in the Department of Pediatrics, Rajshahi Medical College Hospital over a period of 24 months from July 2015 to June 2017. If a child’s age at presentation was between 2 to 8 years of age group of either sex having typical features of nephrotic syndrome(first attack), such as- generalized swelling which started from the face, having abnormal urinary finding ( proteinuria 3+ or more and UTP >1gm/m2/24hrs hypoalbuminemia, hypercholesterolemia but responded to steroid was included in the study. When the child was in remission, serum Lipid profile was done following 10 hours of fasting once again. Then the child was followed up fortnightly for a period of six months from the initial attack for generalized edema and bedside urinary albumin 3+ or more. Results were tested with independent ‘t’ test and χ2 test to find out the association between high lipid profile during remission with the relapse . A two-tailed P value of 0.05 was considered statistically significant. Results: All 50 children were divided into two groups on the basis of lipid profile during remission. Group-1 consists of 20 children who had normal lipid profile during remission and group-2 consists of 30 children who had abnormal lipid profile during remission. Both group-1 & 2 had higher mean levels of serum cholesterol, LDL, and TG levels during initial diagnosis. During remission, group-2 patients showed higher mean serum cholesterol (364.60±64.00 mg/dl vs. 189.25±9.02 mg/dl), serum LDL (241.53±58.42 mg/dl vs. 146.65±3.60 mg/dl), and serum TG (225.10±43.79 mg/dl vs. 138.90±8.15 mg/dl). All these differences in lipid profile between these group were statistically highly significant (p=<0.001).Only 2(10%) cases underwent relapse from group-1 out of 20 cases, whereas 16(53.33%) cases underwent relapse out of 30 cases from group-2 within six (6) months follow-up. The difference between group-1 & group-2 was statistically significant (p=0.002).Among the relapsers, mean cholesterol (394.18±43.03 mg/dl vs. 329.50±67.81 mg/dl; p= 0.004) was significantly higher than that of non-relapsers of group-2 patients. Conclusion: Elevated lipid level, especially serum cholesterol during remission phase may be associated with subsequent relapse in idiopathic childhood nephrotic syndrome. TAJ 2020; 33(2): 69-75